2020
DOI: 10.1039/d0nh00077a
|View full text |Cite
|
Sign up to set email alerts
|

A brain tumor-homing tetra-peptide delivers a nano-therapeutic for more effective treatment of a mouse model of glioblastoma

Abstract: A new glioblastoma (GBM) targeting peptide is developed and successfully demonstrated the delivery of a nano-therapeutic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 45 publications
1
41
0
Order By: Relevance
“…17,45 Therefore, the release kinetics for both Dox and siRNA observed are suitable for systemic administration and in line with previous pSiNP formulations encapsulating small drug molecules. [46][47][48] For example, increased accumulation of pSiNPs has been observed in a glioblastoma model after 2 h post-intravenous injection, limiting any offtarget toxicity from premature release of held cargo. 46 Thus, for NB-pSiNPs, <10% of Dox was released under physiological conditions after 2 h, which would greatly limit the amount of Dox released prior to accumulation at the tumor site.…”
Section: Biomaterials Sciencementioning
confidence: 99%
See 1 more Smart Citation
“…17,45 Therefore, the release kinetics for both Dox and siRNA observed are suitable for systemic administration and in line with previous pSiNP formulations encapsulating small drug molecules. [46][47][48] For example, increased accumulation of pSiNPs has been observed in a glioblastoma model after 2 h post-intravenous injection, limiting any offtarget toxicity from premature release of held cargo. 46 Thus, for NB-pSiNPs, <10% of Dox was released under physiological conditions after 2 h, which would greatly limit the amount of Dox released prior to accumulation at the tumor site.…”
Section: Biomaterials Sciencementioning
confidence: 99%
“…[46][47][48] For example, increased accumulation of pSiNPs has been observed in a glioblastoma model after 2 h post-intravenous injection, limiting any offtarget toxicity from premature release of held cargo. 46 Thus, for NB-pSiNPs, <10% of Dox was released under physiological conditions after 2 h, which would greatly limit the amount of Dox released prior to accumulation at the tumor site.…”
Section: Biomaterials Sciencementioning
confidence: 99%
“…CPPs are short peptides (less than 30 residues) with low cytotoxicity that have the ability to cross biological membranes, which can be coupled to bioactive molecules to transport them inside cells (375,376). Interestingly, it has been demonstrated that several of these peptides have tumor homing capacities or might be modified to discriminate between tumoral and nontumoral cells, thus, when coupled to PPIs-modulators, they would reduce undesired off-target effects and improve their cellular uptake (377)(378)(379)(380). Several methods have been developed to provide CPPs with tumoral specificity, such as the use of peptides that naturally bind to tumor-specific cell surface molecules (380,381), peptides that are inactive until modified by a cancer-associated protease or by properties of the tumoral microenvironment (382,383) and those that take advantage of cellular mechanisms dysregulated in tumoral cells (384).…”
Section: Modulation Of Ppis As a Therapeutic Strategy For Breast Cancermentioning
confidence: 99%
“…Interestingly, it has been demonstrated that several of these peptides have tumor homing capacities or might be modified to discriminate between tumoral and non-tumoral cells, thus, when coupled to PPIs-modulators, they would reduce undesired off-target effects and improve their cellular uptake ( 377 380 ). Several methods have been developed to provide CPPs with tumoral specificity, such as the use of peptides that naturally bind to tumor-specific cell surface molecules ( 380 , 381 ), peptides that are inactive until modified by a cancer-associated protease or by properties of the tumoral microenvironment ( 382 , 383 ) and those that take advantage of cellular mechanisms dysregulated in tumoral cells ( 384 ). As we can see, the use of CPPs is a major tool to provide PPI-modulators with tumoral specificity and low side effects.…”
Section: Modulation Of Ppis As a Therapeutic Strategy For Breast Cancermentioning
confidence: 99%
“…), (iii) targeted delivery, and (iv) controlled release with tunable degradation potency [8][9][10][11][12][13]. In particular, the nano-sized pSi, such as pSiNPs, is worth investigating and has gained much attraction in expanding the scope of research, mostly in drug delivery and controlled-release system, on account of its superior properties such as a high loading yield of drugs, facile surface engineering for targeted delivery, selfreporting by intrinsic photoluminescence at the near-infrared region, and high biocompatibility [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%